Controlador robusto H-infinito para sistema fotovoltaico conectado à rede elétrica baseado em inversor multinível em cascata assimétrica - Silva, André Felício de Sousa (2019)
This work presents a robust state feedback H-infinity current controller for a grid-connected single-phase photovoltaic system. The system contains two power stages, where the second stage corresponds to the DC-AC power conversion and is based on a 19-level asymmetrical cascaded multilevel inverter. Even though only the aspects of a single-phase, low power and low voltage photovoltaic system were directly addressed, the methodologies and conclusions described here can be extended to systems of higher voltage and power. The two main purposes of the proposed system is to operate in a grid-connected mode, providing power to a non-linear local load, and to comply with the performance requirements of the most relevant standards and regulations while injecting current in the power utility. To achieve this, a robust controller was developed, which is capable to deal with parametric uncertainties of the system and also presents a good disturbance rejection of the oscillations in the DC capacitors voltages of the inverter. The control strategy is divided in two parts: the control of the first power stage and the control of the current injection in the grid. Regarding the second stage controller, it was designed based on H-infinity optimization and eigenvalue placement problems, formulated through Linear Matrix Inequalities (LMIs). The simulation results were analyzed and indicate that the proposed system is capable to meet the stipulated performance requirements. The performance results of the proposed control system were then compared to the performances of a classical PI controller, regarding the robustness, and to an H-infinity resonant robust controller, with regards of the quality of the energy injected in the power grid utility.